2013
DOI: 10.1126/science.1233151
|View full text |Cite
|
Sign up to set email alerts
|

Lentiviral Hematopoietic Stem Cell Gene Therapy in Patients with Wiskott-Aldrich Syndrome

Abstract: Wiskott-Aldrich Syndrome (WAS) is an inherited immunodeficiency caused by mutations in the gene encoding WASP, a protein regulating the cytoskeleton. Hematopoietic stem/progenitor cell (HSPC) transplants can be curative but, when matched donors are unavailable, infusion of autologous HSPCs modified ex vivo by gene therapy is an alternative approach. We used a lentiviral vector encoding functional WASP to genetically correct HSPCs from three WAS patients and re-infused the cells after reduced-intensity conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

29
851
1
19

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 955 publications
(907 citation statements)
references
References 63 publications
(121 reference statements)
29
851
1
19
Order By: Relevance
“…These include cells that have distinctive behaviors in terms of cell production and lineage bias (Dykstra et al, 2007;Picelli et al, 2013). Hematopoietic stem cells have been demonstrated to exhibit bias toward myeloid, lymphoid, or megakaryocytic lineage upon transplantation of single cells (Dykstra et al, 2007(Dykstra et al, , 2011Morita et al, 2010), on ex vivo barcoding and transplantation of populations (Aiuti et al, 2013;Gerrits et al, 2010;Jordan and Lemischka, 1990;Lemischka, 1993;Lemischka et al, 1986;Lu et al, 2011;Mazurier et al, 2004;Shi et al, 2002;Snodgrass and Keller, 1987), or by retrotransposon tagging of endogenous cells (Sun et al, 2014b). Further, single-cell transplant data have been coupled with single-cell gene expression analysis on different cells to resolve subpopulations with corresponding gene expression and repopulation potential (Wilson et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…These include cells that have distinctive behaviors in terms of cell production and lineage bias (Dykstra et al, 2007;Picelli et al, 2013). Hematopoietic stem cells have been demonstrated to exhibit bias toward myeloid, lymphoid, or megakaryocytic lineage upon transplantation of single cells (Dykstra et al, 2007(Dykstra et al, , 2011Morita et al, 2010), on ex vivo barcoding and transplantation of populations (Aiuti et al, 2013;Gerrits et al, 2010;Jordan and Lemischka, 1990;Lemischka, 1993;Lemischka et al, 1986;Lu et al, 2011;Mazurier et al, 2004;Shi et al, 2002;Snodgrass and Keller, 1987), or by retrotransposon tagging of endogenous cells (Sun et al, 2014b). Further, single-cell transplant data have been coupled with single-cell gene expression analysis on different cells to resolve subpopulations with corresponding gene expression and repopulation potential (Wilson et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…While these VCNs are in line with previous studies from our group and others [36][37][38] it is expected that lower VCNs would be observed in the clinical application based on our previous studies in human CD34+ cells, 23 and clinical trials in other therapeutic areas. 34,39 Unfortunately, no published data is available regarding the protection from the infections in clinical trials with lentiviral vectors encoding for gp91phox. In a previous retroviral gene therapy trial, two patients cleared infections with 4-25% oxidase activity and are clinically well with very low persistent marking level (0.03 and 0.7%) while another succumbed to the infection after losing gene marking.…”
Section: Discussionmentioning
confidence: 99%
“…These results would suggest that a reduced-intensity conditioning, such as the one adopted for previous CGD trials or other diseases, could be used. 34 Our study included a wide distribution of VCN (ranging from 0.3 to 9.8). While these VCNs are in line with previous studies from our group and others [36][37][38] it is expected that lower VCNs would be observed in the clinical application based on our previous studies in human CD34+ cells, 23 and clinical trials in other therapeutic areas.…”
Section: Discussionmentioning
confidence: 99%
“…4,[32][33][34] However, these methods sometimes lack quantitative standards and may not accurately measure clone size in all instances, particularly when restriction enzyme digestion is used to facilitate adapter ligation. 13,17,35 Recently, random DNA shearing by sonication and count of shear site was introduced and appear to have better accuracy and sensitivity.…”
Section: Discussionmentioning
confidence: 99%